The advantages and disadvantages of using a CO2 laser in endoscopic treatment of laryngeal cancer: a literature review - Joanna Urszula Borowik; Katarzyna Anna Kozak; Kinga Justyna Kuśmierczuk; Wojciech Brodowski; Patryk Jawoszek; Piotr Trojanowski (Kazimierz Wielki University, 2019)
Introduction: The use of a carbon dioxide (CO2) laser combined with a microscope has revolutionized the surgical approach in treating larynx lesions. This method is mainly used in malignant and premalignant lesions in the larynx. The CO2 laser is also commonly used to widen the glottis and in palliative surgery. Aim of study: The purpose of our study was to show advantages and disadvantages of using a CO2 laser in surgery for laryngeal cancer while analyzing available literature. Material and methods: An unsystematic review of Polish and English-language scientific literature was carried out. Electronic databases: SCOPUS, Google Scholar and PubMed were searched using keywords: laser surgery, CO2 laser, laryngeal cancer, larynx. Description of the state of knowledge: CO2 laser microsurgery is characterized by precision and a high safety profile. Low tracheotomy rate, preservation of the closed anatomical area of the neck, makes the operation lightly burdening, shortens the time of hospitalization and recovery. Moreover, it minimizes costs and has a positive impact on the quality of life. The disadvantages of using a CO2 laser mainly relate to transient perioperative and postoperative complications. Disturbances in voice emission clearly have a negative impact on functioning in society. The use of a carbon dioxide laser in the presence of anesthetic gases creates the risk of ignition in the respiratory tract, tissue burns or attachment of the endotracheal tube. Conclusions: The use of a CO2 laser in the treatment of larynx lesions has advantages and disadvantages. The benefits of this technique outweigh the rare complications. Side effects are usually minor and transient but may lead to damage to health. It is worth remembering that only early neoplastic lesions are operated with the CO2 laser, which emphasizes the essence of prevention. Key words: laser surgery; CO2 laser; laryngeal cancer; larynx